Characterization of fungi from palm kernel cake (PKC) and the effect of storage temperature on fungi growth - Razali, Siti Mardhiyah; Lee, Hai Yen; Selamat, Jinap; Mahyudin, Nor Ainy (Universiti Putra Malaysia Press, 2018)
The widespread contamination of animal feed with mycotoxin is not a new issue worldwide. Apart from economic loss, mycotoxin can have adverse health effects on humans due to the carcinogenicity, teratogenicity and mutagenicity potential of the toxins. Palm kernel cake (PKC) is the largest animal feed production in Malaysia. PKC is a by-product of palm kernel oil processing and it has been exported as animal feed. The purpose of this study was to isolate and characterise toxigenic fungi cultured in three different media, Dichloran Rose Bengal Chloramphenicol (DRBC) Agar, Dichloran 18% Glycerol (DG18) Agar and Malt Extract Agar (MEA), derived from PKC that is stored under three different temperatures, 4°C, 25°C and 60°C. Identification of fungi was carried out based on macroscopy and microscopy as well as molecular identification. Four mycotoxigenic fungi were found: Aspergillus niger, Aspergillus flavus, Aspergillus fumigatus and Penicilium citrinum. In order to characterise polymorphism of the isolates, RAPD assay was performed using OPA 3 as the primer. The software resulted in a constructed dendrogram that revealed the percentage of similarities between the typable isolates (A. fumigatus, A. niger and P. citrinum) within range from 20% to 80%. The effect of storage temperature on the strains' enumeration is reported in this work. The distributing strains are influenced by the storage temperature of the PKC matrices. The findings clearly show that Aspergillus species profused at 25°C PKC storage, while it was restricted at low and high temperature.